Isolation and identification of Streptococcus mutans from dental caries patients at Thi-Qar province/Iraq - B. Saleh, Manal; Sh. Abd Al-Zahra , Hamza (University of Thi-Qar Journal of Science, 2019)
Dental caries is one of an important common human infectious disease that can lead to loss of tooth structure, it is occur due to the metabolic activation of the plague microorganisms especially Streptococcus mutans bacterium. Eighteen samples from saliva and dental plaque were collected from patients with dental caries active at ages from (7-25) years from Specialized dental hospital and dental clinics at Thi-Qar province during the period from November to December 2016.Thirty-three isolates belong Streptococcus mutans were identified by cultural methods, biochemical tests and Api 20 Strep. system, while twenty-eight isolates identified by using Polymerase Chain Reaction (PCR) technique and sequencing of 16S rRNA gene with 507 bp, whereas by using 16S rRNA gene the result confirmed that these isolates were belong to Streptococcus mutans. The aim of study is Isolation and identification of Streptococcus mutans bacterium from the dental caries and dental biofilm patients at Thi-Qar province by of 16S rRNA gene.